2014
DOI: 10.2134/jeq2013.10.0418
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Approaches of X‐Ray Absorption Spectroscopic and Electron Microscopic Techniques on Zinc Speciation and Characterization in a Final Sewage Sludge Product

Abstract: Integration of complementary techniques can be powerful for the investigation of metal speciation and characterization in complex and heterogeneous environmental samples, such as sewage sludge products. In the present study, we combined analytical transmission electron microscopy (TEM)-based techniques with X-ray absorption spectroscopy (XAS) to identify and characterize nanocrystalline zinc sulfide (ZnS), considered to be the dominant Zn-containing phase in the final stage of sewage sludge material of a full-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 35 publications
4
24
0
Order By: Relevance
“…Counter-intuitively, evidence shows that nano-metal sulfides are not confined to anoxic environments as colloids of ZnS, CdS, and CuS can persist in oxic waters for months, transporting metals between different environments and ecological niches via metal-sulfide associations (Theberge et al, 1997;Rozan et al, 2003;Sukola et al, 2005;Priadi et al, 2012). In addition, recent environmental studies confirmed the presence of ZnS nanoparticles in domestic and industrial sewage and sludge (Lombi et al, 2012;Kim et al, 2014;Ma et al, 2014), and suggested that sulfidation is a dominant process for the dissolved metals in these engineered systems.…”
Section: Introductionmentioning
confidence: 99%
“…Counter-intuitively, evidence shows that nano-metal sulfides are not confined to anoxic environments as colloids of ZnS, CdS, and CuS can persist in oxic waters for months, transporting metals between different environments and ecological niches via metal-sulfide associations (Theberge et al, 1997;Rozan et al, 2003;Sukola et al, 2005;Priadi et al, 2012). In addition, recent environmental studies confirmed the presence of ZnS nanoparticles in domestic and industrial sewage and sludge (Lombi et al, 2012;Kim et al, 2014;Ma et al, 2014), and suggested that sulfidation is a dominant process for the dissolved metals in these engineered systems.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Zn sulfide minerals have only been observed in OW in the few studies using XAS. 6,29 Standard sequential chemical extraction methods underestimate the sulfide fraction, since it is extracted along with OM fractions. 34 Zn species bound to organic species were only present in a minor proportion (12%) in MWFF, thus confirming the minor role played by OM in Zn speciation in OW.…”
Section: Zinc Speciation In Rawmentioning
confidence: 99%
“…Also numerous studies demonstrated the sulfidation of different types of ENMs (e.g. Ag and ZnO) in WWTPs, limiting the release of ionic species (Kim et al, 2014;Kim et al, 2010;Levard et al, 2012). However, due to the obvious differences in the chemistry of stormwater and wastewater, NMs should be expected to undergo different transformations in stormwater systems compared to waste water systems and within WWTPs (Barton et al, 2015;Brar et al, 2010;Doolette et al, 2013;Kaegi et al, 2013;Kaegi et al, 2011), and the rates of these transformation processes are likely to be different, requiring further research.…”
Section: Pathways and Transformations Of Nms In The Urban Environmentmentioning
confidence: 99%